1999
DOI: 10.1007/s007050050540
|View full text |Cite
|
Sign up to set email alerts
|

The barriers to bluetongue virus infection, dissemination and transmission in the vector, Culicoides variipennis (Diptera: Ceratopogonidae)

Abstract: Transmission of bluetongue virus (BTV) by a vector species of Culicoides was studied using immunohistochemistry, virus titration and in vitro transmission tests. Adult female C. variipennis were used from two colonies that are either "transmission competent" or "transmission refractory" after oral infection with BTV. Intrathoracic (i.t.) injection of BTV into the haemocoel always resulted in a fully disseminated infection and transmission of virus in saliva. However, after ingestion of an infectious blood meal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
130
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(143 citation statements)
references
References 30 publications
11
130
2
Order By: Relevance
“…Furthermore, this virus was found to replicate efficiently in vivo in D. melanogaster after removal of W. pipientis infections by treatment with tetracycline. Finally, confocal analysis revealed that, similar to what has been observed in its insect vector (26), BTV replicates in the fat bodies, salivary glands, and proventriculi (foregut-midgut junction) of infected D. melanogaster flies.…”
Section: B Luetongue Virus (Btv) Is An Arbovirus Belonging To the Genussupporting
confidence: 64%
See 1 more Smart Citation
“…Furthermore, this virus was found to replicate efficiently in vivo in D. melanogaster after removal of W. pipientis infections by treatment with tetracycline. Finally, confocal analysis revealed that, similar to what has been observed in its insect vector (26), BTV replicates in the fat bodies, salivary glands, and proventriculi (foregut-midgut junction) of infected D. melanogaster flies.…”
Section: B Luetongue Virus (Btv) Is An Arbovirus Belonging To the Genussupporting
confidence: 64%
“…These data imply that BTV can enter from the basement membrane (e.g., membrane directly in contact with the hemocoel) of foregut cells but not midgut cells. Besides BTV, several other pathogenic arboviruses, including Venezuelan equine encephalitis virus and West Nile virus, have been shown to infect the foregut-midgut junction of their insect vectors (26,29,68). Therefore, infection of this organ may play a major role in the replication cycle of BTV in insects.…”
Section: Discussionmentioning
confidence: 99%
“…These BTVinfected cd T-cell cultures grow continuously, with no obvious CPE. A similar persistent infection of BTV has been demonstrated in some insect cell cultures without shut-off of host cell DNA or protein synthesis (Jennings & Boorman, 1979;Wechsler et al, 1989;Fu et al, 1999) where there was also little or no sign of CPE.…”
Section: Discussionmentioning
confidence: 74%
“…Midges were sorted by sex and females were further sorted by parity status (Dyce 1969, Potter and Akey 1978, Akey and Potter 1979. Transovarial transmission of BLU virus by C. sonorensis has not been shown (Jones and Foster 1971a, Fu et al 1999, and therefore only parous females would be expected to have acquired BLU virus.…”
Section: Methodsmentioning
confidence: 99%